Structural, electronic, and magnetic properties of perpendicularly magnetised Mn2RhSn thin films - Meshcheriakova, Olga; Koehler, Albrecht; Ouardi, Siham; Kondo, Yukio; Kubota, Takahide; Chandra, Shekhar; Karel, Julie; Barbosa, Carlos V.; Stinshoff, Rolf; Sahoo, Roshnee; Ueda, Shigenori; Ikenaga, Eiji; et al. (Journal of Physics D: Applied Physics, 2015)
Epitaxial thin films of Mn2RhSn were grown on a MgO(0 0 1) substrate by magnetron co-sputtering of the constituents. An optimised range of temperature for heat treatment was used to stabilise the tetragonal structure and to prevent the capping Rh layer from diffusing into the Heusler layer. Electronic and magnetic properties were analysed by hard x-ray photoelectron spectroscopy as well as field- and temperature-dependent Hall and resistivity measurements. The measured valence spectra are in good agreement with the calculated density of states. The measured saturation magnetisation corresponds to a magnetic moment of 1 μB in the primitive cell. The magnetisation measurements revealed an out-of-plane anisotropy energy of 89 kJ m-3 and a maximum energy product of 3.3 kJ m-3. The magnetoresistance ratio is 2% for fields of 9 T. The lattice parameter of the compound has a very small mismatch with MgO, which makes it promising for coherent electron tunnelling phenomena.
CRIS-Team Scopus Importer:2023-03-20
Keywords: HAXPES; Heusler compounds; magnetocrystalline anisotropy; magnetoresistance; resistivity; thin films